Cardioprotective Effect of Decorin in Type 2 Diabetes - Chen, Fuqiong; Lai, Jinsheng; Zhu, Yanfang; He, Mengying; Hou, Huiying; Wang, Jin; Chen, Chen; Wang, Dao Wen; Tang, Jiarong (Frontiers in Endocrinology, 2020)
Cardiomyopathy is the leading cause of increased mortality in diabetes. In the present study, we investigated the effects of decorin (DCN) gene therapy on left ventricular function, cardiac inflammation and fibrosis in type 2 diabetes. Type 2 diabetes was induced in male Wistar rats by high fat diet (HFD, 60% of calories as fat) and STZ (20 mg/kg, intraperitoneal). Diabetic rats were divided into (n=6 for each group) the control group, the GFP-treated group and the DCN-treated group, received intravenous injection of saline solution, recombinant adeno-associated viral (rAAV)-GFP and rAAV-DCN, respectively. We evaluated cardiac inflammation, fibrosis, left ventricular (LV) function at 6 months after gene delivery. Results turned out that rAAV-DCN treatment attenuated diabetic cardiomyopathy with improved LV function compared with control animals, which might be related to the reduced cardiac inflammation and fibrosis. These protective effects were associated with TGFβ1 pathway (ERK1/2 and smad-2) and NF-κB pathway, which may due to the decreased activation level of IGF-IR, increased expression of PKC-α and Hsp70. In conclusion, our results show that rAAV-mediated DCN therapy may be beneficial in the treatment of diabetic Cardiomyopathy